PERAN ORANG TUA DALAM PENDIDIKAN REMAJA (Suatu Kajian di Jorong Piruko Utara Kenagarian Sitiung Kecamatan Sitiung Kabupaten Dharmasraya) - Pramuti, Febrina Widya; Kasih, Fitria; Jarudin, Jarudin (Bimbingan dan Konseling, 2014)
The background of the reseach is the teenager commonly came together at night, mean while the same or different gender. This condition happen when unproperly time. This cases happen because their parent do not attention and monitoring toward their child or teenager, so that they use this condition as come together and have fun with their friends. The purpose of this reseacrh to describe: first, The parent roles in teenager attitude education, second, The parent roles in teenager religion education. This research is describtive qualitative and the location in Jorong Piruko Utara Kenagarian Sitiung Kecamata Sitiung Kabupaten Dharmasraya. The main informant is 8 people (4 people are man and 4 people woman), and 4 teenager as support informant. The informant using purposive sampling technique. In the collecting of the data by interview and data analysis with steps: first, Reduction of data, second, Delivering of data, third, Conclusion. The result of this research: first, The parent toles in teenager attitude education, that found the parent donât have roles in habitual and give a good models, second, The parent roles in teenager religion education, the parent donât give a models in implementation about religion education.